IMPLEMENTASI AKAD MURABAHAH BIL WAKALAH PADA PRODUK PEMBIAYAAN (Penelitian di Koperasi Simpan Pinjam dan Pembiayaan Syariah Al-Uswah Banjar) - Repa Nur Elisa; Ahmad Agung (Syari'ah Economics, 2019)
This study aims to determine (1) the mechanism for using murabahah bi wakalah contracts for KSPPS members; (2) benefits of murabahah bil wakalah financing contract for members of KSPPS Al-Uswah Banjar; (3) the implementation of the murabahah bil wakalah contract on the financing product of KSPPS Al-Uswah Banjar members. This qualitative research uses a case study method. Data collection techniques used direct observation to the KSPPS Al-Uswah office, conducting interviews with managers, employees and customers who carried out murabahah financing at KSPPS Al-Uswah, and relevant documentation. The results of the study illustrate that the mechanism of the murabahah bil wakalah financing contract in KSPPS the contract that is carried out first is the wakalah contract, the benefits of the murabahah bil wakalah financing contract for members are to provide an easy process in terms of financing and help SMEs that need business capital, and the implementation of the murabahah bil contract. wakalah at KSPPS Al-Uswah Banjar has not been in line with DSN MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning murabahah in the first stipulation paragraph 9 states, "if the bank wants to represent the customer to buy goods from a third party, the murabahah sale and purchase contract must be made after the goods in principle become the property of the bank." Then the contract that must be carried out first is the wakalah contract, after that the murabahah contract is carried out. However, the implementation at KSPPS Al-Uswah wakalah contract was signed after the murabahah contract and carried out at one time.